Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/trf.13889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hepatitis E virus nucleic acid test screening platforms and RNA prevalence in French blood donors

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 6 publications
2
23
1
Order By: Relevance
“…Samples can be screened in MP or ID format. The most commonly used assays in blood screening are the Procleix HEV assay (95% LoD 7.89 IU/mL; Panther testing system; Grifols Diagnostic Solutions, Inc., developed in collaboration with Hologic, Inc.) [previously described 11, 15] and the Cobas HEV PCR assay (95% LoD 18.6 IU/mL; Cobas 6800/8800 systems; Roche Molecular Systems, Inc.) [28]. The RealStar HEV RT-PCR kit® for donation screening (95% LoD 4.7 IU/mL; Altona Diagnostics, Hamburg, Germany) is also used by some blood establishments [32].…”
Section: Overview Of Eu Blood Donor Screening Methods and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples can be screened in MP or ID format. The most commonly used assays in blood screening are the Procleix HEV assay (95% LoD 7.89 IU/mL; Panther testing system; Grifols Diagnostic Solutions, Inc., developed in collaboration with Hologic, Inc.) [previously described 11, 15] and the Cobas HEV PCR assay (95% LoD 18.6 IU/mL; Cobas 6800/8800 systems; Roche Molecular Systems, Inc.) [28]. The RealStar HEV RT-PCR kit® for donation screening (95% LoD 4.7 IU/mL; Altona Diagnostics, Hamburg, Germany) is also used by some blood establishments [32].…”
Section: Overview Of Eu Blood Donor Screening Methods and Strategiesmentioning
confidence: 99%
“…A number of HEV screening strategies have been employed between 2012 and 2015, including ID-NAT, MP-6, and MP-96, yielding an overall reactivity rate of 1: 1,616 donations (Table 3). MP-96 screening (2012; RealStar RT-PCR kit, Altona; 1: 2,218) was reduced to MP-6 in 2014 (RealStar RT-PCR kit, Altona; 1: 1,317) [28]. Since January 2018, selective MP-6 screening is performed using the Procleix HEV assay [Gallian P., pers.…”
Section: Overview Of Eu Blood Donor Screening Methods and Strategiesmentioning
confidence: 99%
“…Blood safety is today on the highest safety level, especially for transfusion-transmitted virus infections such as HCV, HIV-1 and HBV due to the introduction of high-sensitive NAT and serological 4th-generation diagnostic systems [42][43][44][45]. New emerging pathogens such as hepatitis E virus, chikungunya virus and dengue virus are still relevant in some regional parts of the world and can be in principle also screened by NAT or serology [46][47][48]. Compared to this, high safety level bacterial contaminations are still a challenge in transfusion medicine and are different from virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty‐two contaminated blood products were transfused, leading to HEV infection in recipients in 42% of cases . In France, the prevalence of positive HEV viraemia in blood donors is estimated to be 1/800 . A French study reported 23 cases of transfusion‐transmitted infections between 2006 and 2016, including 14 with chronic hepatitis in immunosuppressed patients …”
Section: Epidemiologymentioning
confidence: 99%
“…8 In France, the prevalence of positive HEV viraemia in blood donors is estimated to be 1/800. 9 A French study reported 23 cases of transfusion-transmitted infections between 2006 and 2016, including 14 with chronic hepatitis in immunosuppressed patients. 10 In the developed countries, acute hepatitis E usually affects middle aged and elderly men (sex ratio of 4/1, median age 55) often with excessive alcohol consumption.…”
Section: Epidemi Ologymentioning
confidence: 99%